A Study on Basic Education with Special Preference of Mahatma Gandhi ji - Ramakant Sharma; Mayank Sharma (AG Volumes, 2022)
When we talk about "basic education," we're talking about a broad variety of programmes and activities designed to address children's most basic educational requirements. According to the International Standard Classification of Education, elementary and lower secondary education are considered to be part of the basic education category. Pre-primary education and adult literacy programmes are typically included in nations' basic education systems. Providing free and accessible primary education to all people across the world is the primary objective of the Education for All (EFA) movement, which is being spearheaded by UNESCO. The foundation of a peaceful, healthy, and stable world is education, which is a fundamental human right. An individual's whole personality may be developed via education, which includes imparting the knowledge of the ancestors, traditional norms and values, and current science, technology, and conservation. Education fosters the social, economic, and cultural prosperity of human beings and builds an infrastructure for international cooperation via the promotion of mutual understanding and tolerance. As a result, education makes it possible to achieve self-sufficient development and serves as an effective weapon for eradicating poverty in nations all over the globe.